(untitled) (Revista de Ciências Agroveterinárias, 2024)
The semiarid region of Pernambuco produces 99.5% of the forage corn, considering that 93.8% of the ruminant herd is produced in this region of the Brazilian Northeast. The Agreste Meridional is located in this region, which presents seasonality in production due to water deficit. Silage is one of the adopted roughage conservation strategies, with corn being the forage that presents the best indicators when fed to animals. Agronomic aspects are often neglected, considering that the performance of cultivars may vary with the growing environment. The objective of this research was the introduction and evaluation of corn cultivars for the production for whole-plant silage in the Agreste Meridional of Pernambuco, Brazil. The experiment was carried out in a randomized block design, with seven treatments, of which five non transgenic cultivars (‘Alagoano’, ‘Nordestino’, ‘São Luís’, ‘PV2 Viçosense’ and ‘PV1 Branca’) and two transgenic hybrids (‘LG 6030 VT PRO2’ and ‘AS 1573 YG’). It was observed that all genotypes showed susceptibility to Spodoptera frugiperda and Helicoverpa zea, except for the ‘AS 1573 YG’ hybrid, due to the Bt technology. The biometric characters of the genotypes were influenced by the environment. However, with yield of 10,537 and 10,666 kg ha-1 (dry matter), the genotypes ‘Alagoano’ and ‘AS 1573 YG’, respectively, were selected for cultivation in the Agreste Meridional region for the production of silage, which can be used in intensive production systems or family farming.